An assessment of the resources, operations and services of the records management of the Manuel S. Enverga University Foundation - Main Campus and its affiliate campuses within Quezon province - Macapia, Myrna P.; Golfo, Mary Grace P.; Lagrama, Eimee Rhea, C.; Buenrostro-Cabbab, Iyra S. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2014)
Records management seeks to efficiently and systematically control records that are routinely generated as a result of activities and transactions of the institution. This study sought to determine the status of the resources, operations and services of records management of the Manuel S. Enverga University Foundation (MSEUF) Main Campus and its four affiliate campuses in Quezon province. The descriptive method was used to identify the status of records management system of the campuses. Questionnaires were also distributed to the responding department/offices.
The findings of the study revealed that majority of the MSEUF campuses do not have an existing central storage room. Since there is no existing records center, records have been filed in their respective offices. There is also no specific budget allotted to records management. Like other institutions, there is no specific personnel in-charge of recordkeeping in some of the departments/offices. This causes some problems in the retrieval of records. The MSEUF main campus is starting to develop standards in records creation especially in the designs and formats of forms. But some of the offices lack standard controls and procedures in the creation of forms and other records. Almost all of the departments/offices in all MSEUF campuses are sorting records/documents before filing. Majority of the departments/offices used the "labeling and filing in folder" method. Departments/offices filed their documents in folders and then fastened. Records were arranged alphabetically by title. The most common filing equipment/facility that the departments/offices are using are the steel filing cabinet. Most of the offices are using compiled guides as their finding aids. Not all the head of the departments/offices are checking or inspecting their records. They do not monitor the condition of their records to determine what records are obsolete and need to be disposed to give space to the increasing volumes of records due to daily operations. Not all departments/offices in MSEUF campuses have the Records Retention and Disposition Schedule to determine the life of records. Not all clerks/secretaries are knowledgeable in handling records.
The recommendations of this study include the establishment of centralized records center for the semi-active records that could also be a good venue for archival appraisal. There should be a strong and continuous support, both administrative and financial, from the administration for the formation and implementation of records repositories. Standardization of records practices should be developed and implemented in all campuses. Records officers should become knowledgeable about the relevant policies, procedures and processes. Well-trained records officers would be able to facilitate and support the implementation of sound records management practices. Records officers and department heads should always work together in designing programs and policies in terms of records management. A records management committee could also be established to ensure that the set policies and procedures are implemented.
Vita.
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Manuel S. Enverga University Foundation; Universities and colleges -- Records and correspondence -- Management. -- Philippines; Records -- Management